1988
DOI: 10.1111/j.1532-5415.1988.tb04259.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Immediate and 6‐Month Outcomes in Hospitalized Elderly Patients

Abstract: This article presents results of a prospective multivariate study of hospitalized elderly patients at an acute-care Veterans Administration (VA) hospital to identify factors on hospital admission predictive of several short- and long-term outcomes: in-hospital and 6-month mortality, immediate and delayed nursing home admission, length of hospital stay, and 6-month rehospitalization. All patients aged 70 years and over admitted to acute-care beds on the medical service wards during a 1-year period were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
195
4
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(226 citation statements)
references
References 20 publications
22
195
4
5
Order By: Relevance
“…Individual diagnoses were not examined as predictors of mortality because previous studies in older populations have shown that functional measures are stronger predictors of hospital outcomes than medical diagnoses or diagnosis-related groups. 42,43 The inclusion of functional and cognitive measures in our models provided additional control for important prognostic variables, which have been widely recognized to reflect the overall "burden of illness" and to exert substantial prognostic impact on outcomes of hospitalization. 26,[42][43][44] Taken together, the APACHE II, functional, and cognitive measures provide a potent and plausible indicator of illness severity and comorbidity for older hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Individual diagnoses were not examined as predictors of mortality because previous studies in older populations have shown that functional measures are stronger predictors of hospital outcomes than medical diagnoses or diagnosis-related groups. 42,43 The inclusion of functional and cognitive measures in our models provided additional control for important prognostic variables, which have been widely recognized to reflect the overall "burden of illness" and to exert substantial prognostic impact on outcomes of hospitalization. 26,[42][43][44] Taken together, the APACHE II, functional, and cognitive measures provide a potent and plausible indicator of illness severity and comorbidity for older hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…For older patients, hospitalization has been associated with a variety of adverse outcomes, including high rates of functional decline, increased risk of medical and iatrogenic events, and increased likelihood of nursing home placement upon discharge [1][2][3][4][5][6][7][8][9][10]. Low mobility, defined as activity that is limited to a bed or chair, is also a common event during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…2 Decline in function and increasing dependence on assistance with activities of daily living have been strongly associated with hospital admission [6][7][8] and mortality in older adults. [9][10][11][12] The relationship between functional decline and hospital admission raises the possibility that function may contribute to geographic variation in hospital use, either through regional variation in functional debility or regional variation in available treatment resources or practice patterns related to functional decline and disability.…”
Section: Introductionmentioning
confidence: 99%